2012
DOI: 10.4155/fmc.12.58
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Inhibitors of DNA Damage-Repair Pathways: An Approach to Overcome Tumor Resistance to Alkylating Anticancer Drugs

Abstract: A major challenge in the future development of cancer therapeutics is the identification of biological targets and pathways, and the subsequent design of molecules to combat the drug-resistant cells hiding in virtually all cancers. This therapeutic approach is justified based upon the limited advances in cancer cures over the past 30 years, despite the development of many novel chemotherapies and earlier detection, which often fail due to drug resistance. Among the various targets to overcome tumor resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 133 publications
(119 reference statements)
0
20
0
Order By: Relevance
“…DNA damage created by alkylation agents would lead to apoptosis and is one of the major mechanisms of cytotoxic anticancer drugs such as TMZ (61,62). We have demonstrated that rhein inhibits ALKBH2 and ALKBH3 in vitro and synergistically suppresses the proliferation of U87 cells during exposure to MMS (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…DNA damage created by alkylation agents would lead to apoptosis and is one of the major mechanisms of cytotoxic anticancer drugs such as TMZ (61,62). We have demonstrated that rhein inhibits ALKBH2 and ALKBH3 in vitro and synergistically suppresses the proliferation of U87 cells during exposure to MMS (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Finally, the ability of FM-HCR to identify agents that either inhibit or enhance DRC in human cells (Fig. 4 C and D) opens the door to screens for novel compounds that might be used either to potentiate the effects of DNA damage-based anticancer agents or to mitigate the deleterious effects of environmental exposure to DNA-damaging agents (57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%
“…33 On the other hand, DNA repair ability of tumor cells prevents the accumulation of lethal DNA damage from cytotoxic agents and ionizing radiation, which leads to tumor resistance. 34,35 Therefore, DDR plays a central role in tumorigenesis and cancer therapy.…”
Section: Discussionmentioning
confidence: 99%